QoS-aware routing and traffic management in multi-flow opportunistic routing. (September 2021) - Parsa, Ali; Moghim, Neda
Highlight: Opportunistic routing is a new routing paradigm for wireless ad-hoc networks. Quality-of-service based routing improves network delay and throughput. Links quality and nodes congestion are considered to form the QoS routing metric. Queue length can be a network congestion indicator. The links' data rate can be a channel quality indicator. Abstract: Opportunistic routing (OR) is a new routing paradigm in which the next hop forwarders are not fixed. A group of network nodes called forwarder set is considered as potential forwarders from which the next hop will be selected. Although OR can improve network performance, network resources are allocated to the flows, regardless of their quality-of-service (QoS) needs. This paper proposes a QoS-aware opportunistic routing that considers QoS levels of the flows in passing them over appropriate paths. To achieve this goal, we propose a method that selects and prioritizes the forwarder set based on the flow's QoS levels. This policy leads to a more uniform distribution of traffic in the network. Consequently, the average queue length, the average queuing delay, and packet loss are reduced. The simulation results imply that the proposed algorithm makes traffic distribution more uniform so that the network performance is improved in terms of average throughput and end-to-end delay.